2022
DOI: 10.1108/jsm-12-2021-0488
|View full text |Cite
|
Sign up to set email alerts
|

Can Alexa serve customers better? AI-driven voice assistant service interactions

Abstract: Purpose This study aims to examine customers’ willingness to engage in service interactions enabled by artificial intelligence (AI) controlled voice assistants (VA). Drawing on the tenets of dual-factor theory, this study measures the impact of both enablers and inhibitors – mediated by trust in Alexa – on customers’ intentions to transact through VAs. Design/methodology/approach Data from a survey of 290 users of VAs from Japan was collected through “Macromill”. The authors used a covariance-based path anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 76 publications
3
10
0
Order By: Relevance
“…In the following sections, we will examine the individual contributions. Malodia et al (2022) address customers' willingness to engage in service interactions enabled by artificial intelligence (AI) controlled voice assistants (VA). The authors build on dualfactor theory (DFT), by measuring the impact of enablers and inhibitorsmediated by trust in Alexaon customers' intentions to transact through voice assistants.…”
Section: Contribution Of the Special Issue Articles To Interdisciplin...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the following sections, we will examine the individual contributions. Malodia et al (2022) address customers' willingness to engage in service interactions enabled by artificial intelligence (AI) controlled voice assistants (VA). The authors build on dualfactor theory (DFT), by measuring the impact of enablers and inhibitorsmediated by trust in Alexaon customers' intentions to transact through voice assistants.…”
Section: Contribution Of the Special Issue Articles To Interdisciplin...mentioning
confidence: 99%
“…Besides, extant research mainly examined the drivers of consumer VA adoption, while studies on their inhibitors are limited. Meanwhile, identification of the inhibitors is equally important, and one of the studies in this special issue (Malodia et al , 2022) has addressed this gap in the context of service exchanges. Specifically, the authors measured the impact of both enablers and inhibitors on customers’ intentions to transact through voice assistants and found that convenience and status-seeking act as enablers and positively influence trust in VAs, whereas risk barrier acts as an inhibitor and negatively influences trust in VAs.…”
Section: A Roadmap For Future Interdisciplinary Services Marketing Re...mentioning
confidence: 99%
“…Hence, trust is one of the most pivotal antecedents for engaging technology (Lu et al, 2016). The literature is replete with examples of trust as a significant determinant in different kinds of relationships in Information Systems (Foehr & Germelmann, 2020; Malodia et al, 2023). Moreover, trust is considered a positive predictor of attitude (Pitardi & Marriott, 2021).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…First, most research has examined simple, single functions carried out by SVAs, for example, when the devices are asked to answer direct questions or execute easy tasks. Nevertheless, little research has analysed the role of SVAs as new purchase recommendation agents for consumers during the decision-making process (see, as an exception, Flavi an et al, 2023; Malodia et al, 2023). When an individual has to make a purchase decision, (s)he can directly interact with a SVA on an ongoing and personal basis, asking for information, seeking advice and obtaining recommendations based on her/his preferences and habits.…”
mentioning
confidence: 99%
“…Hernandez-Ortega and Ferreira, 2021;Mishra et al, 2022). Although these scholars showed a substantial understanding of the adoption stage, they overlooked the influence of other mediating variables that might operate during consumer-SVA interactions, such as trust in SVAs' purchase recommendations and brand engagement (Malodia et al, 2023;Melumad, 2023).…”
mentioning
confidence: 99%